Development of a Biology Learning Media-Flipped Classroom Model Using Edpuzzle - Septie Nurrokhmah; R Mursid; Dina Ampera (RIRAI Publisher, 2024)
This research and development aims to produce biology learning media using the flipped classroom model with Edpuzzle that is feasible, practical, and effective in improving student learning outcomes on excretory system material. This type of research is development research using the ADDIE development model with stages: (1) analysis stage, (2) design stage, (3) development stage, (4) implementation stage, and (5) evaluation stage. The research results show: (1) Material expert validation test that the material in the media developed is very worthy with an average score of 88.72%. (2) The Instructional Design Expert validation test is very worthy, with an average score of 96.87%. (3) The Media Expert validation test is very worthy, with an average score of 94.20%. (4) Individual trials are very worthy, with an average score of 87.73%. (5) The small group trial was very feasible, with an average score of 90.90%. And (6) field trials are very worthy of an average score of 90.20%. The practicality test by very practical teachers had an average score of 90.20%, while the practicality test results for students had an average score of 94.90%, which was in the very practical category. Using the flipped classroom model, biology learning media with Edpuzzle in the experimental class got an average learning outcome of 89.68, while students who were taught without this media got an average score of 69.14. Testing the hypothesis using the independent t-test, there is a significant difference between classes taught using the flipped classroom model of biology learning media with Edpuzzle and classes taught without using this media.